NOX4/NADPH oxidase expression is increased in pulmonary fibroblasts from patients with idiopathic pulmonary fibrosis and mediates TGFβ1-induced fibroblast differentiation into myofibroblasts. Issue 8 (4th August 2010) - Amara, Nadia; Goven, Delphine; Prost, Fabienne; Muloway, Rachel; Crestani, Bruno; Boczkowski, Jorge
Abstract : Background: Persistence of myofibroblasts is believed to contribute to the development of fibrosis in idiopathic pulmonary fibrosis (IPF). Transforming growth factor β1 (TGFβ1) irreversibly converts fibroblasts into pathological myofibroblasts, which express smooth muscle α-actin (α-SMA) and produce extracellular matrix proteins, such as procollagen I (α1). Reactive oxygen species produced by NADPH oxidases (NOXs) have been shown to regulate cell differentiation. It was hypothesised that NOX could be expressed in parenchymal pulmonary fibroblasts and could mediate TGFβ1-stimulated conversion of fibroblasts into myofibroblasts. Methods: Fibroblasts were cultured from the lung of nine controls and eight patients with IPF. NOX4, α-SMA and procollagen I (α1) mRNA and protein expression, reactive oxygen species production and Smad2/3 phosphorylation were quantified, in the absence and in the presence of incubation with TGFβ1. Migration of platelet-derived growth factor (PDGF)-induced fibroblasts was also assessed. Results: It was found that (1) NOX4 mRNA and protein expression was upregulated in pulmonary fibroblasts from patients with IPF and correlated with mRNA expression of α-SMA and procollagen I (α1) mRNA; (2) TGFβ1 upregulated NOX4, α-SMA and procollagen I (α1) expression in control and IPF fibroblasts; (3) the change in α-SMA and procollagen I (α1) expression in response to TGFβ1 was inhibited by antioxidants and by a NOX4 small interfering RNA (siRNA); (4) NOX4 modulated α-SMA and procollagen I (α1) expression by controlling activation of Smad2/3; and (5) NOX4 modulated PDGF-induced fibroblast migration. Conclusion: NOX4 is critical for modulation of the pulmonary myofibroblast phenotype in IPF, probably by modulating the response to TGFβ1 and PDGF.